INCLUSIVE APPROACHES TO INTEGRATING SOCIAL RESPONSIBILITY INTO ORGANIZATIONAL POTENTIAL MANAGEMENT (INNOVATIVE ECONOMY, 2024)
Pshybelskyi V.V., Tsymbaliuk S.M., Solovianchyk I.V. INCLUSIVE APPROACHES TO INTEGRATING SOCIAL RESPONSIBILITY INTO ORGANIZATIONAL POTENTIAL MANAGEMENTPurpose. The aim of the article is to determine the role of inclusive approaches to social responsibility in enhancing the efficiency of organizational potential management, analysing their impact on the development of organizational potential components such as human, innovative, financial, and reputational resources, and substantiating the significance of inclusive and socially responsible practices in ensuring sustainable development and competitiveness of organizations.Methodology of research. The study employed the following methods: abstract and logical – for formulating theoretical conclusions regarding the concept of social responsibility and its inclusive aspects; theoretical analysis and synthesis – for exploring the impact of socially responsible and inclusive practices on the components of organizational potential; and a systematic approach – to identify interconnections between social responsibility, inclusive approaches, and the key components of organizational potential.Findings. It was established that social responsibility ensures a systematic positive impact on key components of organizational potential, including human, innovative, financial, and marketing potentials. The integration of inclusive approaches into socially responsible practices further amplifies this effect by engaging vulnerable population groups in economic activities and enhancing the efficiency of human capital utilization. Contemporary theoretical approaches to social responsibility and inclusivity were analysed, along with the experience of leading companies in implementing socially responsible practices. It was proven that the integration of socially responsible and inclusive initiatives contributes to more effective resource utilization, enhanced corporate reputation, the formation of ethical and inclusive corporate cultures, and long-term business sustainability.Originality. The systematization of the impact of social responsibility and inclusive approaches on the components of organizational potential was further developed, substantiating their role as an integral element of management that ensures the achievement of strategic goals, engagement of diverse social groups, and organizational adaptation to external challenges.Practical value. The research results can be applied to develop organizational management strategies focused on integrating social responsibility and inclusivity into business processes, thereby enhancing competitiveness, reputational capital, and sustainable development. The study’s recommendations can be adapted to the specifics of sectoral and local markets, contributing to the formation of socially oriented and inclusive business models.Key words: social responsibility, inclusive approaches, organizational potential management, sustainable development, corporate culture, innovative potential, reputation, inclusivity, veterans’ reintegration, resource management, management.
Keywords: social responsibility; inclusive approaches; organizational potential management; sustainable development; corporate culture; innovative potential; reputation; inclusivity; veterans’ reintegration; resource management; management.